Empowering Generation Z as Agents of Change and Eliminating Cancer Stigma Through Digital Campaigns - Syahri, Alfi; Widya, Fadhilah Aliyyah; Alma Dinisa, Atsir; Viliana, Chornelia Dina; Arista, Meli Nor; Putri Nabila, Yulisa; Puteri, Amanda Selvia; Ximenes, Herminia dos Santos (Journal of Health Community Service, 2025)
Public stigma towards cancer patients remains high, negatively affecting theirpsychological well-being, leading to depression, anxiety, and reduced self-esteem.Stigma is influenced by knowledge levels, and digital campaigns serve as a tool toreduce it by disseminating accessible and reliable information. PalliApis Care, anorganization leveraging social media platforms to educate the public about cancer,conducted this study targeting Generation Z. The campaign was implemented through aquantitative Zoom meeting using a one-group pretest-posttest design. A total of 200participants from across Indonesia joined the campaign, with a majority being women(87.8%). Participants were predominantly aged 18-22 years (80.2%), followed by thoseaged 23-27 years (19.1%), and 12-17 years (0.8%). The pretest average score was 70.00,while the posttest score increased to 82.96, showing a knowledge gain with a meandifference of 12.96 (p = 0.000, p < 0.05). The results confirmed that social media-baseddigital campaigns effectively raise awareness and shift public perceptions of cancerstigma. Challenges related to misinformation were addressed through digital literacytraining for Generation Z. In addition to enhancing knowledge, the campaign providedpsychological support to cancer patients by sharing survivor narratives. Generation Zacted as agents of change, using digital skills to spread accurate information and fosteran inclusive environment for patients. This program demonstrates that engagingGeneration Z in health campaigns not only improves health literacy but also contributesto sustainable efforts in reducing social stigma. The program’s long-term impact lies inthe continuous involvement of Generation Z in public health initiatives.